3-(3-Hydroxy-4-methoxyphenyl)-4-(3, 4, 5-trimethoxyphenyl)-1, 2, 5-selenadiazole (G-1103), a novel combretastatin A-4 analog, induces G2/M arrest and apoptosis by disrupting tubulin polymerization in human cervical HeLa cells and fibrosarcoma HT-1080 cells. (5th February 2015) - Zuo, Daiying; Guo, Dandan; Jiang, Xuewei; Guan, Qi; Qi, Huan; Xu, Jingwen; Li, Zengqiang; Yang, Fushan; Zhang, Weige; Wu, Yingliang
Highlights: G-1103 is a new 3, 4-diaryl-1, 2, 5-selenadiazol analog of combretastatin A-4. G-1103 behaves as a tubulin inhibitor. G-1103 exhibits potent anticancer properties against HeLa and HT-1080 cells. G-1103 induces G2/M phase arrest and apoptosis in HeLa and HT-1080 cells. The mechanisms of G-1103 induced apoptosis in two cell lines are different. Abstract: Microtubule is a popular target for anticancer drugs. In this study, we describe the effect 3-(3-hydroxy-4-methoxyphenyl)-4-(3, 4, 5-trimethoxyphenyl)-1, 2, 5-selenadiazole (G-1103), a newly synthesized analog of combretastatin A-4 (CA-4), showing a strong time- and dose-dependent anti-proliferative effect on human cervical cancer HeLa cells and human fibrosarcoma HT-1080 cells. We demonstrated that the growth inhibitory effects of G-1103 in HeLa and HT-1080 cells were associated with microtubule depolymerization and proved that G-1103 acted as microtubule destabilizing agent. Furthermore, cell cycle analysis revealed that G-1103 treatment resulted in cell cycle arrest at the G2/M phase in a time-dependent manner with subsequent apoptosis induction. Western blot analysis revealed that down-regulation of cdc25c and up-regulation of cyclin B1 was related with G2/M arrest in HeLa and HT-1080 cells treatment with G-1103. In addition, G-1103 induced HeLa cell apoptosis by up-regulating cleaved caspase-3, Fas, cleaved caspase-8 expression, which indicated that G-1103 induced HeLa cell apoptosis was mainly associated with death receptor pathway. However, G-1103 induced HT-1080 cell apoptosis by up-regulating cleaved caspase-3, Fas, cleaved caspase-8, Bax and cleaved caspase-9 expression and down-regulating anti-apoptotic protein Bcl-2 expression, which indicated that G-1103 induced HT-1080 cell apoptosis was associated with both mitochondrial and death receptor pathway. Taken together, all the data demonstrated that G-1103 exhibited its antitumor activity through disrupting the microtubule assembly, causing cell cycle arrest and consequently inducing apoptosis in HeLa and HT-1080 cells. Therefore, the novel compound G-1103 is a promising microtubule inhibitor that has great potentials for therapeutic treatment of various malignancies.